Penguatan Karakter Siswa di Era Society 5.0 untuk Mewujudkan Generasi Cerdas dan Berintegritas - Iqbal; Nurjannah; Syafriadi; Saputri, Yuni; Nurdiana; Mauliza, Suci (Yayasan Sagita Akademia Maju, 2025)
Strengthening student character is an important effort in forming a generation that is intelligent and has integrity, especially in the Society 5.0 era which is marked by technological advances and the industrial revolution. This community service report aims to provide understanding to students at SMAN 2 Indrajaya, class 3 of SMA, regarding the importance of character in facing global challenges. This service involves lecturers and students of the Pancasila and Citizenship Education Study Program, using learning methods based on discussions, lectures and character values ​​simulations. The results of the activity show that students can better understand the importance of moral values, ethics and responsibility in everyday life. It is hoped that this character formation can support the creation of a generation that is not only intelligent in academic aspects, but also has high integrity.